Penerapan Sistem Akuntansi Pemerintahan dalam Mendukung Akuntabilitas Kinerja Instansi Pemerintah (AKIP) : Penerapan pada Pusat Analisis Sosial Ekonomi dan Kebijakan Pertanian Bogor. - Pamungkas, Bambang; Yusuf, Eddy Supriyadi (Jurnal Ilmiah Ranggagading (JIR), 2007)
Organizing government finance in an exact time became a part of the effort to strengthening system in a country. Good system as a system which is can be conducting consistently, monitoring regularly and reducing mismanagement in organizing government finance. The weakness of government regulation became a major factor that causing all those mismanagement factors. The objectives of accounting system were : (a) to protect government assets and their institution, (b) providing an accurate and exact information about government finance in one institution and government as a whole, which is very valuable for planning, organizing and controlling all the activities and government finances efficiently. The study using descriptive method to positioning the analysis of secondary data to elaborate the activity of government accounting implementation and itâs relationship with the designing of Government Institution Accountability Report. The implementation of accounting system in Indonesian Center For Agriculture Socio Economic And Policy Studies in principle has been conduct inline with the regulation, in fact in practice the problems keep appear caused by bureaucratic and human related errors, how ever. Evaluation and auditing budget activity is good solution for the problems keep appear bureaucratic and human related errors. Keywords: budget, system, performance